Climate Change Variability and its Impacts in Nepal (Journey for Sustainable Development and Peace Journal, 2023)
This paper aims to explore the climate variability in agriculture and discuss adaptation. Climate change has been an issue in relation to water, agriculture, and ultimately livelihood in the community. It impedes the ecosystem of nature and society. In Nepal, the temperature growth rate is increasing day by day and it reached 0.180C which contributes to climate change variability and it is contributing to the scarcity of water and hence, the impact on agricultural production. Similarly, only a small amount of available water (4.7%) in Nepal has been effectively utilized. The majority of households in Nepal depend upon agriculture and livestock. The imbalance in agriculture production is also directly related to nutrition and health. Many parts of the Karnali province have been faced with food deficiency and malnutrition. Due to the challenges, the proper utilization and sustainable use of water sources for securing food security in Nepal is imperative.